Città strategiche L'amministrazione dell'area metropolitana - Donati, Daniele (Studi di diritto pubblico, 2023)
The administration of metropolitan cities is a complicated issue that, in every country, has forced legislators and interpreters to face problems previously unseen. This complexity, descending by the uniqueness of those places, imposes to law scholars an analysis not limited to the study of their necessarily differentiated forms of government and management. Moving beyond the mere consideration of the material element of the Territory and it's role in identifying the voters community, it's necessary to explore and understand the cutting-edge dynamics that agitate in urban centers: assuming this point of view, the book debates, also in a comparative and historical perspective, what is here labeled as "the metropolitan issue". Starting from the unresolved determination of their role in a multilevel system, here is scrutinized the actual legal framework of these local authorities, situated in an intermediate position between regions and municipal bodies, offering a review of the possible alternative interpretations, but holding firm the idea of metropolitan cities as aimed primarily at the strategic planning of the economic and social development of the whole area. The result is their characterization as systemic entities, more capable of relationships than regulation, whose autonomy has been attributed and has to be interpreted and evaluated in the key of efficiency in performances and satisfaction of those who live and work in those places.